Pengaruh Sikap Menabung Dan Orientasi Masa Depan Terhadap Perencanaan Dana Pensiun Pada Pekerja Swasta Di Kota Surabaya - Muhammad Arfan Hajam (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2020)
The purpose of this research was to determine the effect of saving attitudes and future orientation on retirement planning Population in this research are private workers in the city of Surabaya. The sample in this research used 200 samples. The data collection techniques used questionnaires. The data analysis technique used SEM-PLS. The result of this research is that saving attitude and future orientation influences retirement planning with a percentage of influence of 26%, while the remaining 74% is influenced by other variables that are not included in this research model.